Pengaruh Likuiditas, Aktivitas, dan Leverage Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Infrastruktur Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Fadjri, Triyudha Akmal; Hakim, Heikal Muhammad Zakaria (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of liquidity as measured by current ratio, activity as measured by total asset turnover ratio, and leverage as measured by debt to equity ratio partially and simultaneously on the profit growth of infrastructure sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The samples in this study are selected using the purposive sampling technique with the total of 18 sample companies. This study applies quantitative analysis methods using descriptive and verification techniques. The hypotheses are tested using multiple regression analysis models. The results of this study indicate that liquidity, activity, and leverage ratios partially have a significant effect on profit growth. Then liquidity, activity and leverage simultaneously or combined also have a significant effect on profit growth in infrastructure sector companies listed on the Indonesia Stock Exchange for the period 2018-2022.